Fearless Conversations School Leaders Have to Have : Step Out of Your Comfort Zone and Really Help Kids. - Jones, Irving C., Sr (SAGE Publications, 2017)
Step out of Your Comfort Zone and Really Help Kids To meet the needs of today's learners, fearless leadership is required to support and empower the adults who work with these learners. Written to help leaders build a culture of learning and improve academic achievement for all students, this guide to recognizing and using strategies will encourage staff to work at their full potential, build trust, and strengthen collegiality. Readers will find interviews and case studies to illustrate effective practice strategies to help them move from traditional methodologies toward stronger transforma.